Low-Intensity Pulsed Ultrasound Alleviates Hypoxia-Induced Chondrocyte Damage in Temporomandibular Disorders by Modulating the Hypoxia-Inducible Factor Pathway - Tao Yang; Chao Liang; Lei Chen; Lei Chen; Jun Li; Jun Li; Wei Geng (Frontiers Media S.A., 2020)
Temporomandibular disorders are a common cause of chronic pain in the orofacial region and have a complex and multi-factorial pathophysiology. Mechanical loading or inflammatory conditions have been shown to decrease oxygen tension within the joint cartilage and activate the hypoxia-inducible factor (HIF) pathway, which in turn aggravates the pathological processes underlying temporomandibular joint (TMJ) disorders. We previously showed that low-intensity pulsed ultrasound (LIPUS) treatment effectively repairs TMJ injury induced by chronic sleep deprivation (CSD). Here, we explored the effects of LIPUS treatment on hypoxia-induced chondrocyte injury. We found that it effectively restored the proliferation capacity of mandibular chondrocytes under hypoxic conditions and lowered their rate of apoptosis. Chondrogenic capacity, as assessed by type II collagen levels, and mucin-positive areas were also significantly increased after LIPUS treatment. Levels of matrix metalloprotein-3 and interleukin-6 decreased in mandibular chondrocytes following this treatment, whereas the expression of tissue inhibitor of metalloproteinase-1 increased. We also found that HIF-1α expression was upregulated in mandibular chondrocytes under hypoxic conditions and was further enhanced by LIPUS treatment. Similarly, HIF-2α levels increased in mandibular chondrocytes under hypoxic conditions but decreased following LIPUS treatment. Subsequently, we established a CSD-induced TMJ injury model and found that LIPUS increased mucin-positive areas as well as HIF-1α expression and decreased HIF-2 level in the chondrocyte layer. Together, our results indicate that the protective effect of LIPUS on chondrocyte is partly associated with the HIF pathway.